How Taxes Can Contribute to the Implementation of the Public Governance Strategy? – An Analysis for Eastern European Countries - Vlad, Cristina; Ibadula, Birol; Brezeanu, Petre (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The paper begins with a short literature review regarding the public governance concept in the EU approach and its methods for establishing a common way to manage different situations for all member states; we discovered that the problems they confront with have to do with good governance and qualitative public administration. In the second part, we developed an econometric model for three Eastern European countries and we found a strong correlation between the total revenues from taxes and social contributions and total gross debt in 2002-2014 period. We ended the paper by emphasizing the conclusions obtained.